S81 Feasibility and uptake of enhanced smoking cessation services within ambulatory HIV care. (12th November 2015) - Kyriacou, C; Stewart, N; Melville, A; Brown, J; Edwards, K; Lloyd, R; Johnson, M; Flint, J; Rodger, A; Lipman, M
Abstract : Background: HIV infected individuals are at increased risk of smoking-related illness and smoking rates amongst populations with HIV are often significantly higher than the general population. Interventions that reduce the prevalence of smoking in this population are urgently required. Aims: We sought to establish the impact of initiating regular smoking screening and advice by healthcare assistants (HCAs) or nurses as part of routine care appointments in a HIV ambulatory care service. Methods: Individuals attending for ambulatory HIV care appointments were asked brief screening questions regarding cigarette smoking by Healthcare Assistants (HCAs) or nurses. This was completed whilst clinical observations were performed, allowing this intervention to be delivered as part of routine care. Those who were current smokers were given Very Brief Advice (VBA) regarding smoking cessation and offered referral to smoking cessation services. The number of referrals to smoking cessation services was compared to the six months prior to the introduction of the enhanced service. Results: 1, 031 individuals were screened between October 2014 and March 2015: 262 (25%) reported that they were current smokers. 248 (93%) of these smokers were provided with VBA and the opportunity of referral to smoking cessation services. Of these, 103 (38%) accepted referral compared to 6 referrals from the HIV outpatient service in the preceding 6 months. Conclusions: An intervention to ask service users about smoking and provide smoking cessation advice can be undertaken as part of routine care in an ambulatory HIV care service and is effective in identifying smokers and increasing referrals to smoking cessation services. Further work will evaluate the impact of this intervention in HIV positive subjects.